An Implementation of Portfolio System in Writing Class: Middle Education Teachers’ Experience - Tungga Pramudya Utama; Sumardi Sumardi; Slamet Supriyadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The portfolio system exists as one alternative answer for a challenge encountered by an English teacher. The research about the portfolio system that focused on middle education teachers' perception is quite necessary since it helps the teachers and students of the English language find a proper way of learning writing skills. This study aimed to investigate the middle education teachers' perception of using a portfolio system to improve writing ability in teaching writing skills in English as a foreign language to junior high school students. The participants of this research were four junior high school teachers. In conducting this case study, the researcher collected data from the interview. This research found that the teachers favored implementing a portfolio system to improve students’ English writing skills. This research stands as a contribution to teaching English writing skills. This study suggests that a portfolio system is a useful tool for teaching English writing skills in middle education. The teachers were to facilitate the students by applying the portfolio system and giving feedback on their writing to encourage their writing performance.